Impact of Spinal Ganglia Cryoextract Introduction on Contractile Activity of Uterine Myometrium of Late Reproductive Age Rats - Nesteruk, Hanna; Legach, Evgen (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 291